Automatic Real-Time Barcode Localization in Complex Scenes - Zhang, Chunhui; Wang, Jian; Han, Shi; Yi, Mo; Zhang, Zhengyou (Proceedings of the International Conference on Image Processing (ICIP 2006), 2006)
Many applications exist for automatically finding and reading barcodes in complex scenes with a camera. The key problem is to search barcodes in a complex scene and supply them for a reading subsystem. However, illumination, rotation, perspective distortion and multiple barcodes circumstances make barcode localization difficult. By jointly analyzing texture and shape, we propose a realtime barcode localization method that is robust to the above problems. A user only needs to put a barcode in front of a camera at around 15 cm for common Web cameras, and the system then automatically locates and decodes the barcode. This paper only focuses at automatic localization. We will demonstrate the complete system live at the conference.